2004
DOI: 10.1021/jp0481310
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Dynamics of H2O+ (D2O+) + NH3 Studied with Crossed Molecular Beams and Density Functional Theory Calculations

Abstract: The charge transfer and proton transfer reactions between H 2 O + (D 2 O + ) and NH 3 were studied at collision energies below 1 eV using the crossed molecular beam technique and density functional theory (DFT) calculations. The reaction products include NH 3 D + formed by deuterium ion transfer, NH 3 + produced by charge transfer, and NH 2 D + formed by charge transfer with H/D exchange. These three products are formed in the ratio of 1.0:2.0:1.2, respectively. The center of mass flux distributions of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The proton transfer and charge transfer products are clearly formed in large impact parameter collisions, suggesting that the centrifugal barrier associated with the long-range attractive potential of the approaching reactants prevents the reactants from reaching the short range part of the potential where C-O bond formation occurs. In previous works, 4,5,[23][24][25] we have shown that the electrostatic complexes that characterize reactions proceeding through large impact parameters decay with rates near 10 14 s −1 , further suggesting that processes that may occur via slow isomerization pathways will result in product levels below the detection limit.…”
Section: Computational Studiesmentioning
confidence: 67%
See 1 more Smart Citation
“…The proton transfer and charge transfer products are clearly formed in large impact parameter collisions, suggesting that the centrifugal barrier associated with the long-range attractive potential of the approaching reactants prevents the reactants from reaching the short range part of the potential where C-O bond formation occurs. In previous works, 4,5,[23][24][25] we have shown that the electrostatic complexes that characterize reactions proceeding through large impact parameters decay with rates near 10 14 s −1 , further suggesting that processes that may occur via slow isomerization pathways will result in product levels below the detection limit.…”
Section: Computational Studiesmentioning
confidence: 67%
“…The proton transfer process forming C 2 H 3 + exhibits many characteristics of direct proton transfer that we have studied recently in this laboratory. [3][4][5][23][24][25]31 This proton transfer reaction is another example of a heavy+ light-heavy ͑H+LH͒ system in which a light particle, H, is transferred between heavier molecular fragments. The potential energy surface for this transfer, expressed in scaled and skewed coordinates, 32 is characterized by a very acute angle, 18°, between the entrance and exit channels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were also reported in the D 2 O + +NH 3 system previously studied in our laboratory. 25 The explanation for this small but unusual decrease in the incremental translation of the products may arise from the possibility that the bent configurations in the current system become increasingly important at higher energies, leading to additional rotational excitation in the fragments. The corner cutting trajectories that produce vibrationally excited products at lower collision energies are replaced by trajectories at higher translational energy that are more effective at reaching the compressed configurations that facilitate translation in the separating products.…”
Section: Discussionmentioning
confidence: 97%
“…In many of the systems investigated by Farrar and co-workers, charge transfer is dominant over proton transfer. Through a variation of the charge state (OH +/À + C 2 H 2 ) 69,70 or the proton donor (H 2 O + /H 3 O + + NH 3 ), 71,72 they were able to investigate the proton transfer dynamics. A direct stripping mechanism was found to be the only reaction pathway.…”
Section: Charge Transfer and Hydrogen Transfer In Heavy-light Heavy Rmentioning
confidence: 99%